Pelayanan Kefarmasian dan Pemahaman Penggunaan Obat Rasional (POR) di Kota Denpasar: Pharmaceutical Services and The Understanding of Rational Use of Medicine (RUM) in Denpasar City - Arimbawa, Putu Eka (Bali Medika Jurnal, 2020)
The pharmaceutical practice is essential in giving health information services, and this is because of the lack of knowledge about the rational use of medicine (RUM) in the community. This study aimed to see the relationship between pharmaceutical services with the understanding of RUM. This study uses a cross-sectional survey design. The number of samples used was 97. Data were collected from January to February 2020 in Denpasar City using a questionnaire. Data were analyzed using the binary logistic test. The results showed that excellent pharmaceutical services are drug queuing-collection systems (61.9%) and completeness of the equipment used (38.1%). Most people understand the RUM must adjust to the patient's condition (93.8%). The pharmaceutical services provide a significant relationship with the understanding of RUM (P<0.05). Pharmaceutical services of the drug queue system and completeness of the equipment can improve patients' knowledge of RUM of clinical conditions. The comprehensiveness of the drug and the pharmacist's readiness needs special attention in developing information patent-generic drug. Therefore, it is necessary to evaluate the presence and the right number of pharmacists in providing pharmaceutical services in the community.